Of Knights, Priestesses, and Colonial Soldiers : 20th Century Catholic Youth and Historical Memory - Cuplinskas, Indre (. Revue d'histoire ecclésiastique. - Louvain : Université Catholique, 1900-. - Online-Ressource. - ISSN 2294-1088 118, 2023)
This paper compares the construction of social memory by three early 20th-century Catholic youth movements: the Association catholique de la jeunesse canadienne-française in French-speaking Canada, Quickborn in Germany, and Ateitis in Lithuania. These movements - nationalist, Catholic and young - have been examined primarily in their respective national contexts. This comparative study investigates the differences in the importance the movements gave to the construction of social memory and the extent to which these activities shaped the organisations' engagement of the public sphere. The study also shows that harnessing the past was a gendered activity. Lastly, the comparison sheds light on the variety of ways that Catholic discourse and rituals were engaged in the creation of social memory